2013
DOI: 10.1351/pac-con-12-10-05
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired catalytic reactions with vitamin B12 derivative and photosensitizers

Abstract: As part of a study directed toward design of good catalytic systems based upon a hydrophobic vitamin B 12 , heptamethyl cobyrinate perchlorate, we describe the preparation of various nanomaterials using the vitamin B 12 derivative and photosensitizers. Examples include vitamin B 12 -hyperbranched polymers (HBPs), human serum albumin (HSA) containing vitamin B 12 derivatives, a vitamin B 12 -titanium dioxide hybrid catalyst, a vitamin B 12 -Ru complex combined system, and a vitamin B 12 -rose bengal combined sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…It is well known that removing the second chlorine atom is much more difficult than the rst one from DDT molecules. According to the literature, for B 12 -based photocatalysts, B 12 -BVIm-Ru copolymer 7 and B 12 -HAS articial enzyme, 34 which are comparable to that used in this work, although they all showed enhanced photocatalytic activities with $100% conversion of DDT, few didechlorinated products were detected. From the above comparison, it can be concluded that the B 12 -PIL/rGO hybrid possessed very high photocatalytic activity for DDT dechlorination, especially for its didechlorination, in the presence of the photosensitizer Ru(bpy) 3 Cl 2 , and the introduction of rGO signicantly enhanced the reaction efficiency.…”
Section: The Catalytic Performance Of the Hybrid Catalyst B 12 -Pil/rgosupporting
confidence: 71%
“…It is well known that removing the second chlorine atom is much more difficult than the rst one from DDT molecules. According to the literature, for B 12 -based photocatalysts, B 12 -BVIm-Ru copolymer 7 and B 12 -HAS articial enzyme, 34 which are comparable to that used in this work, although they all showed enhanced photocatalytic activities with $100% conversion of DDT, few didechlorinated products were detected. From the above comparison, it can be concluded that the B 12 -PIL/rGO hybrid possessed very high photocatalytic activity for DDT dechlorination, especially for its didechlorination, in the presence of the photosensitizer Ru(bpy) 3 Cl 2 , and the introduction of rGO signicantly enhanced the reaction efficiency.…”
Section: The Catalytic Performance Of the Hybrid Catalyst B 12 -Pil/rgosupporting
confidence: 71%
“…Dechlorination is one of the biomimetic reactions catalysed by vitamin B 12 thus utilizing halogenated derivatives in B 12 -catalyzed reactions is often plagued by the formation of a significant amount of dehalogenated products. [34][35][36][37][38][39][40][41]50] In accordance, the reaction with thioester 8 possessing the chlorine substituent afforded desired product 14 in only 23 % yield in contrast to 64 % for the respective bromide. For substrates with more reactive benzyl substituents the competing dehalogenation predominated under optimized conditions, for thioester S-pyridin- 2-yl-3-(chloromethyl)benzothioate (11) product 22 formed in only 29 % yield, while substrate (10) with benzyl bromide moiety was entirely dehalogenated affording product 23.…”
Section: Resultsmentioning
confidence: 84%
“…Based on the photosensitization of redoxactive B12 derivatives, Hisaeda and coworkers have recently developed various bio-inspired reactions for the degradation of organohalide pollutants such as DDT and related compounds according to eq. 3 under visible light exposure [79,80].…”
Section: Figmentioning
confidence: 99%